Experimental Study on Dynamic Resilient Modulus of Lime-Treated Expansive Soil - Zheng Lu; Yang Zhao; Shaohua Xian; Hailin Yao (Advances in Materials Science and Engineering)
Dynamic resilient modulus is the design index of highway subgrade design code in China, which is significantly affected by the traffic loads and environmental changes. In this study, dynamic triaxial tests were conducted to investigate the influence of moisture content, compaction degree, cyclic deviator stress, and confining pressure on lime-treated expansive soil. The suitability of UT-Austin model to lime-treated expansive soils was verified. The results indicate that the dynamic resilient modulus of lime-treated expansive soils increases nonlinearly with the increase of compaction degree, while decreases nonlinearly with the increase of dynamic stress level. The dynamic resilient modulus decreases linearly with the increase of moisture content and increases linearly with the increase of confining pressure. Moreover, the moisture content has a more significant effect on the dynamic resilient modulus of lime-treated expansive soil. Therefore, it is necessary to ensure the stability of soil humidity state and its excellent mechanical properties under long-term cyclic loading for the course of subgrade filling and service. Finally, the calculated results of the UT-Austin model for dynamic resilient modulus show a good agreement with the test results.